Magnetic resonance imaging improves stratification of fibrosis and steatosis in patients with chronic liver disease. - Lee, Han Ah; Kim, Seung-seob; Choi, Jin-Young; Seo, Yeon Seok; Park, Beom Jin; Sim, Ki Choon; Kim, Seung Up (Abdominal Radiology, 2022)
Purpose: We aimed to compare the diagnostic accuracy of magnetic resonance imaging (MRI) and transient elastography (TE) in assessing liver fibrosis and steatosis in patients with chronic liver disease (CLD). Methods: Patients who underwent liver biopsy or liver surgery at two academic hospitals between 2017 and 2021 were retrospectively recruited. The stages of liver fibrosis and steatosis were evaluated using histologic examination. Liver stiffness (LS) was assessed using MR elastography (LSMRE) and TE (LSTE). Liver steatosis was assessed using proton density fat fraction (PDFF) and controlled attenuation parameter (CAP). Results: The mean age of the study population (n = 280) was 53.6 years and male sex predominated (n = 199, 71.1%). Nonalcoholic fatty liver disease was the most prevalent (n = 127, 45.5%), followed by hepatitis B virus (n = 112, 40.0%). Hepatocellular carcinoma was identified in 130 patients (46.4%). The proportions of F0, F1, F2, F3, and F4 fibrosis were 13.2%, 31.1%, 9.6%, 16.4%, and 29.7%, respectively. LSMRE had a significantly greater AUROC value than LSTE for detecting F2–F4 (0.846 vs. 0.781, P = 0.046), whereas LSMRE and LSTE similarly predicted F1–4, F3–4, and F4 (all P > 0.05). The proportions of S0, S1, S2, and S3 steatosis were 34.7%, 49.6%, 12.5%, and 3.2%, respectively. PDFF had significantly greater AUROC values than CAP in predicting S1-3 (0.922 vs. 0.806, P < 0.001) and S2-3 (0.924 vs. 0.795, P = 0.005); however, PDFF and CAP similarly predicted S3 (P = 0.086). Conclusion: MRI exhibited significantly higher diagnostic accuracy than TE for detecting significant fibrosis and mild or moderate steatosis in patients with CLD.